2020
DOI: 10.1016/j.heliyon.2020.e03740
|View full text |Cite
|
Sign up to set email alerts
|

Production of graphene nanoplate/polyetheretherketone composites by semi-industrial melt-compounding

Abstract: Current studies on nanocomposites have focused on their multifunctional properties and their industrial production. In this work, polyetheretherketone (PEEK)/graphene nanoplate (GNP) composites were produced by a direct semi-industrial process. Different percentages of untreated GNP (1, 5, and 10 wt.%) were added to PEEK by employing melt-compounding followed by injection-moulding. Despite the semi-industrial approach used, the modulus, strength, and Poisson coefficient of the nanocomposites (1 and 5 wt.%) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…When the content of graphene is more than 5 wt %, the tensile modulus, ultimate tensile strength, and fracture strain of the nanocomposites remain steady. Similar increases and decreases have been reported with graphene-PEEK nanocomposites 40,41 and other polymer nanocomposites. 42 Compared with the mechanical properties of PEEK, the tensile modulus of the GNP-5/PEEK nanocomposite is improved by 12.8%, and its ultimate tensile strength and fracture strain are weakened by 33 and 86.5%, respectively.…”
Section: Mechanical Properties Of Peek and Gnps/peeksupporting
confidence: 86%
See 1 more Smart Citation
“…When the content of graphene is more than 5 wt %, the tensile modulus, ultimate tensile strength, and fracture strain of the nanocomposites remain steady. Similar increases and decreases have been reported with graphene-PEEK nanocomposites 40,41 and other polymer nanocomposites. 42 Compared with the mechanical properties of PEEK, the tensile modulus of the GNP-5/PEEK nanocomposite is improved by 12.8%, and its ultimate tensile strength and fracture strain are weakened by 33 and 86.5%, respectively.…”
Section: Mechanical Properties Of Peek and Gnps/peeksupporting
confidence: 86%
“…The tensile modulus, ultimate tensile strength, and fracture strain of PEEK are 3.99 GPa, 113 MPa, and 21.4%, respectively, which makes an agreement with previous studies. 40,41 It can also be found that as the content of graphene increases from 0 to 5 wt %, the tensile modulus of the nanocomposites gradually increases, while the ultimate tensile strength and fracture strain of nanocomposites significantly decrease. When the content of graphene is more than 5 wt %, the tensile modulus, ultimate tensile strength, and fracture strain of the nanocomposites remain steady.…”
Section: Mechanical Properties Of Peek and Gnps/peekmentioning
confidence: 94%
“…8. It is clear from Table 2 that incorporation of EG into PEEK does not significantly affect the glass transition temperature of the composites 63 …”
Section: Resultsmentioning
confidence: 97%
“…Not performed Not performed [27] In the present study, G referenced PEEK nanocomposites were produced through melt compounding and injection moulding and the effect of G loading on the properties of the resulting composites has been investigated thoroughly using a wide range of characterization techniques. The biocompatibility and tissue regeneration ability of the composites has also been evaluated in vitro and in vivo.…”
Section: Not Specifiedmentioning
confidence: 99%
“…Table 1 Recent studies on PEEK and its composite systems with graphene modification [27] In the present study, G referenced PEEK nanocomposites were produced through melt compounding and injection moulding and the effect of G loading on the properties of the resulting composites has been investigated thoroughly using a wide range of characterization techniques.…”
Section: Introductionmentioning
confidence: 99%